2012
DOI: 10.1021/jf204497b
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin-3-O-(3″-O-methyl)-gallate Content in Various Tea Cultivars (Camellia sinensis L.) and Its in Vitro Inhibitory Effect on Histamine Release

Abstract: It has been reported that epigallocatechin-3-O-(3″-O-methyl)-gallate (EGCG3″Me) and the EGCG3″Me-rich green tea ( Camellia sinensis L.) cultivar 'Benifuuki' exhibit antiallergic effects. The objective of this study was to investigate the effect of various tea leaf catechins on histamine release from murine bone marrow mast cells (BMMC). At a dose of 50 μg/mL, the rank order of histamine release inhibition was observed to be epicatechin-3-O-(3″-O-methyl)-gallate (ECG3″Me) > gallocatechin-3-O-(3″-O-methyl)-gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…In addition, an increased anti-allergic effect has been reported for methylated EGCG and other catechins relative to the unmethylated forms [216]. On the other hand, other studies have reported a decrease in the antioxidant activity of methylated catechins [217].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 99%
“…In addition, an increased anti-allergic effect has been reported for methylated EGCG and other catechins relative to the unmethylated forms [216]. On the other hand, other studies have reported a decrease in the antioxidant activity of methylated catechins [217].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 99%
“…Previous studies have demonstrated that one consumption of green tea extract 1.5-4.5 g or 1-3 cups by healthy individuals results in plasma concentrations of EGCG of only 4 µM 29 . The ingestion of benifuuki tea, which contains O-methylated catechin, results in higher EGCG blood concentrations and may have a more bene cial effect than other green teas 30 . It is necessary to devise an effective means to administer EGCG, such as O-methylated EGCG, because it will be dif cult to immediately use EGCG in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to anthocyanins, four delphinidin and four cyaniding glycosides were determined by high-performance liquid chromatography (HPLC), as described in our previous report (15). In addition to these ingredients, catechin, caffeine and amino acid levels in the tea samples were also measured by HPLC, as described in previous reports (16,17). The contents of flavonol glycosides, catechins, anthocyanins, caffeine and amino acids in each green tea sample are shown in Table 1.…”
Section: Green Tea Samplesmentioning
confidence: 99%